Dynamics and oligomerisation of ABCG2 investigated using various fluorescence techniques - Wong, Kelvin (2015)
The human ABCG2 (second member of ABC transporter G-subfamily) is an important ATP-dependent exporter in the body with broad substrate specificity including xenobiotics (e.g. anticancer agents) and endogenous compounds (e.g. sterols and lipids). ABCG2 was first discovered in a multidrug resistant breast cancer cell line and it is suggested to cause resistance to chemotherapy in certain cancers such as acute myeloid leukaemia and small cell lung cancer. Physiologically, ABCG2 is found in the protective sanctuary sites of the body, for instance the gut and blood-brain-barrier, affecting pharmacokinetics and treatment efficacies of small molecule drugs. Structurally, the polypeptide chain of ABCG2 contains a single nucleotide binding domain and a single transmembrane domain, which is half the number of domains required for a fully functional ABC transporter. Although many have suggested that ABCG2 function as dimer or higher order oligomer, studies so far have been unable to convincingly address the oligomeric state of ABCG2.